Smart Manufacturing: Integration of Industry 4.0 Technologies to Enhance Engineering System Productivity - Simon, Gusman; Wedono, Bramono Wangsa (Journal of Renewable Engineering, 2026)
The transformation of manufacturing systems in the era of Industry 4.0 has led to the emergence of smart manufacturing, which integrates advanced technologies such as Internet of Things (IoT), cyber-physical systems (CPS), artificial intelligence (AI), and digital twins to enhance engineering system productivity. This study aims to analyze how the strategic integration of these technologies improves productivity by addressing system complexity, integration challenges, and human factors. The research employs a qualitative approach using a systematic literature review (SLR) method, with data collected from reputable international journals published between 2020 and 2025. The analysis is conducted through thematic and comparative synthesis to identify key patterns and relationships. The findings indicate that the integration of Industry 4.0 technologies significantly improves operational performance, including increased efficiency, reduced downtime, enhanced product quality, and improved system responsiveness. However, challenges such as integration complexity, legacy systems, and workforce skill gaps remain critical barriers. The study concludes that a holistic and strategic integration approach, supported by strong data governance and workforce development, is essential to achieve sustainable productivity improvements in engineering systems.